Pembangunan Jalan dan Pendirian Malino sebagai Pusat Pemerintahan dan Wisata di Sulawesi Selatan (1921-1931) - Wins Senor (Jurnal Riset Multidisiplin Edukasi, 2026)
This article traces the history of road infrastructure development and the early growth of tourism in Malino, South Sulawesi, during the period 1921–1931, based on a critical analysis of Dutch colonial archives. The study employs historical research methods through the interpretation of primary sources in the form of administrative documents of the Netherlands Indies government. The analysis focuses on the dynamics of planning and constructing the Makassar–Sindjai connecting road that traversed the mountainous Parigi region, with Malino serving as a strategic node. The article reveals that the motivations behind the project were multidimensional, encompassing administrative and politioneel (order and security) interests, economic objectives related to the transportation of agricultural products, as well as the development of a herstellings- en ontspanningsoord (convalescent and recreational resort) for European officials and tourists. Although the construction relied heavily on forced labor (heerendienst) and contributions from indigenous communities and faced significant natural and technical challenges, it ultimately succeeded in transforming Malino not only into a new local administrative center but also into the nucleus of a modern tourist destination. This study concludes that Malino’s transformation was a product of colonial policy aimed at consolidating power while simultaneously exploiting the economic and recreational potential of the highlands, leaving a legacy of infrastructure and tourism patterns that persist to the present day.